The Ethics of Visual Culture - Bucar, Elizabeth M. (Journal of religious ethics, 2016)
To introduce this set of essays on visual ethics, I address the conceptual and methodological contours, as well as difficult theoretical questions, that might emerge with a visual turn in religious ethics. In addition I situate the work represented in this focus issue within ongoing conversations about moral perception, culture as a topic of normative analysis, and the various roles of visual culture in the moral life.